Z badań nad pochodzeniem i motywacją zwrotu wieszać psy na kimś, na czymś - Ignatowicz-Skowrońska, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The phrase wieszać psy ‘to bad-mouth someone’ is found in four languages: Polish, Ukrainian, Belarussian and Russian. Its first actualizations in the Polish language appear in the works of writers connected to the Polish Eastern Borderlands and are characterized by syntactic variability. Moreover, both in Polish and in local East Slavic dialects the words pies, Ukrainian and Russian собакa and Belorussian сабакa mean ‘the flower of burdock’. One has to conclude that the phrase is a dialecticism developed at the Polish-Belarussian-Ukrainian borderlands and popularized in general language by authors attached to these areas.